Strategi Guru Pendidikan Pancasila dan Kewarganegaraan (PPKn) dalam Mencegah Cyberbullying di SMA Negeri 1 Sidoarjo - Devina Safira Prastowo; Rr. Nanik Setyowati (Universitas Negeri Surabaya (Unesa), 2023)
This study aims to find out what strategies are used by Pancasila and Citizenship Education Teachers at Senior High School 1 Sidoarjo in preventing the phenomenon of cyberbullying. This study uses a qualitative method with a phenomenological approach. The informants were two teachers of Pancasila and Citizenship Education from Senior High School 1 Sidoarjo. This study uses the structuration theory of Anthony Giddens which stated that globalization has changed most of the ways of human life which of course has certain consequences. Consequences faced by Indonesia today include the moral degradation of student as a result of advances in information and communication technology, one of which the phenomenon of cyberbullying. The data analysis techniques used is an interactive model from Miles and Huberman based on mapping or description of the data. The results of this study indicate that Pancasila and Citizenship Education Teachers at Senior High School 1 Sidoarjo are already aware of cyberbullying phenomenon and have collaborated with various parties to prevent cyberbullying in Senior High School 1 Sidoarjo students. This team will also receive special guidance from Pancasila and Citizenship Education Teachers. The motive that the informant wanted to addres in the process of preventing cyberbullying was to make students of Senior High School 1 Sidoarjo wiser in using the internet, considering that Pancasila and Citizenship Education subjects were very important in the formation of nation and character building which would later form capable citizens think critically but also act responsible. Keywords: Strategy, Pancasila and Citizenship Teacher, Cyberbullying